1958
DOI: 10.1136/bjo.42.8.501
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations in Idiopathic Hyperlipaemia and Xanthomatosis

Abstract: THE accumulation of neutral fac in the blood to such an extent as to produce turbidity of the serum is termed hyperlipaemia. This may occur physiologically after a fatty meal, secondarily to diabetes mellitus, the nephrotic syndrome and glycogen storage disease, or idiopathically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1958
1958
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…2 This condition is usually associated with high TG levels>1000 mg/dL. 3 Abnormal deposition of TG produces a salmon-coloured fundus associated with creamish discolouration of retinal arteries and veins in the advanced stages. The disease usually begins in the periphery and progresses towards the centre as the TG levels increase.…”
Section: Descriptionmentioning
confidence: 99%
“…2 This condition is usually associated with high TG levels>1000 mg/dL. 3 Abnormal deposition of TG produces a salmon-coloured fundus associated with creamish discolouration of retinal arteries and veins in the advanced stages. The disease usually begins in the periphery and progresses towards the centre as the TG levels increase.…”
Section: Descriptionmentioning
confidence: 99%
“…Various studies have demonstrated that lipemia retinalis is associated with high TG levels in hyperlipoproteinemias types 1, 3, 4, and 5 with different underlying causes 11. Specifically, the genetic mutation in the primary LPL gene produced the type 1 hyperlipoproteinemia seen in this case.…”
Section: Discussionmentioning
confidence: 73%
“…The ocular findings are due to the light scattering from the triglyceride-laden chylomicrons in the plasma. Lipemia retinalis is estimated to be present in 23% of patients with severe hypertriglyceridemia, as a consequence of the accumulation of circulating chylomicrons caused by lipoprotein lipase deficiency (1).…”
Section: Case Reportmentioning
confidence: 99%
“…Lipemia retinalis is a rare presentation of hypertriglyceridemia described as a white and creamy appearance of the retinal arteries and veins, and sometimes the whole fundus (1). Although secondary and genetic factors can elevate triglyceride (TG) levels, metabolic syndrome remains the most common cause of hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%